Nucleolar organizer regions indicators hepatocytes in experimental thyrotoxicosis - V. S. Botasheva; N. A. Stadnyk (Кубанский научный медицинский вестник, 2014)
On laboratory animals receded experimental model of hyperthyroidism. Work carded out on 46 white male rats of Wistar weighing 250-300 g. Laboratory animals administered daily L-thyroxine in a dose of 1,6 mg per 1 kg of body weight. Rats were taken out of the experience through 7, 14, 21, 28, 45, 60 and 90 days. To determine the level of thyroid hormone blood sampling was carried out from tail vein. Conducted macroscopic and microscopic examination of the liver. The experimental results showed that the daily administration of L-thyroxine observed increase in the level of thyroid hormones (T4, T3) in the blood and a decrease in thyroid stimulating hormone (TSH). Histological examination of the liver revealed diffuse hydropic and ballooning degeneration of hepatocytes, colliquative necrosis areas with the formation of cavities, diffuse perisinusoidal edema, lymphocytic infiltration. When stained with nitro acid silver identified nucleolar organizers. Marked increase in the number of nucleolar organizer regions in experimental thyrotoxicosis on the 28th day and the gradual reduction of the end of the experiment.